2018
DOI: 10.1007/s11481-018-9818-1
|View full text |Cite
|
Sign up to set email alerts
|

Most Current Smokers Desire Genetic Susceptibility Testing and Genetically-Efficacious Medication

Abstract: The clinical translation of genetic research on nicotine dependence and treatment response requires acceptance of genetic testing by smokers. This study determines (1) which current smokers are receptive to genetic susceptibility testing for nicotine dependence and (2) to what potential extent smokers motivated to quit desire to take smoking cessation medication when hypothetical genetic results predict their pharmacogenetic medication response. Current smokers from a genetic nicotine dependence study (n = 130… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 18 publications
2
16
0
Order By: Relevance
“…Data suggest that many people have an interest in genetic testing for psychiatric conditions (Chiu et al, 2018;DeLisi & Bertisch, 2006;Gamm, Nussbaum, & Biesecker, 2004;Laegsgaard, Kristensen, & Mors, 2009;Meiser et al, 2008;Scott et al, 2014;Tercyak, Peshkin, Wine, & Walker, 2006;Wilde, Meiser, Mitchell, & Schofield, 2010), with most studies reporting that over 80% of the sample is interested (Chiu et al, 2018;DeLisi & Bertisch, 2006;Laegsgaard et al, 2009;Meiser et al, 2008;Scott et al, 2014). This high level of interest is consistent with interest in genetic testing for other health outcomes, including breast cancer (Lerman, Seay, Balshem, & Audrain, 1995), prostate cancer (Bratt et al, 2000), and weight gain (Meisel, Walker, & Wardle, 2012).…”
Section: Interest In Genetic Feedbackmentioning
confidence: 75%
See 3 more Smart Citations
“…Data suggest that many people have an interest in genetic testing for psychiatric conditions (Chiu et al, 2018;DeLisi & Bertisch, 2006;Gamm, Nussbaum, & Biesecker, 2004;Laegsgaard, Kristensen, & Mors, 2009;Meiser et al, 2008;Scott et al, 2014;Tercyak, Peshkin, Wine, & Walker, 2006;Wilde, Meiser, Mitchell, & Schofield, 2010), with most studies reporting that over 80% of the sample is interested (Chiu et al, 2018;DeLisi & Bertisch, 2006;Laegsgaard et al, 2009;Meiser et al, 2008;Scott et al, 2014). This high level of interest is consistent with interest in genetic testing for other health outcomes, including breast cancer (Lerman, Seay, Balshem, & Audrain, 1995), prostate cancer (Bratt et al, 2000), and weight gain (Meisel, Walker, & Wardle, 2012).…”
Section: Interest In Genetic Feedbackmentioning
confidence: 75%
“…Interest in genetic testing for psychiatric conditions does not appear to vary across individuals' racial/ethnic background (Chiu et al, 2018;Scott et al, 2014;Tercyak et al, 2006). Two studies found that individuals of minority racial/ethnic backgrounds were less interested in psychiatric genetic testing; however, these racial/ethnic differences were not statistically significant after accounting for other confounding demographic variables (Chiu et al, 2018;Tercyak et al, 2006).…”
Section: Race/ethnicitymentioning
confidence: 98%
See 2 more Smart Citations
“…7,8) were more likely to undergo lung cancer screening, use nicotine replacement therapy, and quit smoking. Further enthusiasm for these specific precision approaches is bolstered by evidence of their acceptability among smokers (10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%